The Influence of (Dis)belief in Free Will on Immoral Behavior - Caspar, Emilie A.; Vuillaume, Laurène; Magalhães De Saldanha da Gama, Pedro A.; Cleeremans, Axel (Frontiers in Psychology, 2017)
One of the hallmarks of human existence is that we all hold beliefs that determine how we act. Amongst such beliefs, the idea that we are endowed with free will appears to be linked to prosocial behaviours, probably by enhancing the feeling of responsibility of individuals over their own actions. However, such effects appear to be more complex than one might have initially thought. Here, we aimed at exploring how induced disbeliefs in free will impact the sense of agency over the consequences of one’s own actions in a paradigm that engages morality. To do so, we asked participants to choose to inflict or to refrain from inflicting an electric shock to another participant in exchange of a small financial benefit. Our results show that participants who were primed with a text defending neural determinism — the idea that humans are a mere bunch of neurons guided by their biology — administered fewer shocks and were less vindictive towards the other participant. Importantly, this finding only held for female participants. These results show the complex interaction between gender, (dis)beliefs in free will and moral behaviour.